Interference protection mechanism for LTE-Advanced radio access networks supporting dynamic spectrum access - Naranjo, Juan Diego; Bauch, Gerhard; Saleh, Abdallah Bou; Viering, Ingo; Halfmann, Rudiger (2013 IEEE Wireless Communications and Networking Conference (WCNC), 2013)
Spectrum licensing schemes are subject to fixed allocation, little sharing and long term holding, which is leading to the current problem of false scarcity. Considering current spectrum allocation methodologies and given the exponential growth of traffic demand, spectrum scarcity becomes problematic since in the near future current radio access technologies will not be able to cope with this traffic demand increase anymore. Thus, new licensing schemes must be designed to enable sharing of spectrum frequency, so that rarely used spectrum channels can be reallocated dynamically between primary users and mobile services. Cognitive radio based dynamic spectrum access is foreseen as a solution to this intricate problem. Further, simple dynamic spectrum access schemes could be integrated into an LTE-Advanced mobile network, making use of carrier aggregation and the standardized user equipment measurement reports. In this paper, we focus on geographical division of spectrum for an LTE-Advanced network, where the spectrum is classified into Frequency/Location/Time bundles. These bundles work as independent tradeable units that can be aggregated and tailored to the needs of the participants in spectrum adjudication. Geographic locations are divided into a square grid, where an estimation of the Radio Environment Map based on propagation parameters is used to assess the sets of tradeable units assigned to a given mobile network operator. Furthermore we make an analysis of how spectrum exclusion areas can be characterized and defined in order to coexist with the operator's network.